Justified. The complete first season [videorecording (DVD)] - Olyphant, Timothy; Searcy, Nick; Carter, Joelle; Pitts, Jacob; Zea, Natalie, 1975-; Leonard, Elmore, 1925-2013 (Sony Pictures Home Entertainment, 2011)
Due to his old-school style, U.S. Marshal Raylan Givens is reassigned from Miami to his childhood home in the poor, rural coal-mining towns in Eastern Kentucky. Lawman Givens is a tough, soft-spoken gentleman who never gives an inch.